Hyperledger Fabric-Based Post Quantum Cryptography for Healthcare Application Using Discrete Event Simulation - Tamara Zhukabayeva; Ateeq Ur Rehman; Nargis Tariq; Elhadj Benkhelifa (IEEE Access)
The centralized data sharing challenges in healthcare have spurred the adoption of distributed methods, including blockchain technology, to enhance security and privacy. This paper proposes a blockchain-based healthcare system leveraging post-quantum cryptography (PQC) to secure sensitive patient data, stored on a permissioned blockchain. Discrete event simulation (DES) is used in the simulation to represent and assess three critical processes: blockchain transactions, patient data requests, and data encryption. We examine the dynamics of blockchain transaction processing, encryption effectiveness, and data access inside the suggested architecture through simulation. The results highlight how post-quantum encryption and blockchain technology can strengthen healthcare data management by resolving important concerns about patient data sharing’s integrity and confidentiality.